2018
DOI: 10.1111/pere.12252
|View full text |Cite
|
Sign up to set email alerts
|

Parents‐in‐law's topic avoidance: Understanding the role of interaction goals and relational characteristics

Abstract: Utilizing dual logic from a multiple goals and relational turbulence theory, this study examined parents‐in‐law's interaction goals for topic avoidance with their children‐in‐law. Data from 159 parents‐in‐law revealed that multiple and conflicting goals were associated with parents‐in‐law's topic avoidance. Furthermore, relational parameters (i.e., relational uncertainty and partner influence) were associated with the goals in‐laws pursued. Results augment theorizing on a multiple goals perspective, relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
(114 reference statements)
3
12
0
Order By: Relevance
“…The associations between uncertainty and message production have been well documented (e.g., Knobloch, 2006; Mikucki-Enyart, 2018a) with fewer studies examining associations between ambiguity and message processing. The handful that have, however, have revealed associations between relational uncertainty and more tentative and pessimistic evaluations of partner’s messages (Knobloch & Solomon, 2005; Knobloch et al, 2007).…”
Section: Theorizing On In-law’s Uncertainty and Message Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…The associations between uncertainty and message production have been well documented (e.g., Knobloch, 2006; Mikucki-Enyart, 2018a) with fewer studies examining associations between ambiguity and message processing. The handful that have, however, have revealed associations between relational uncertainty and more tentative and pessimistic evaluations of partner’s messages (Knobloch & Solomon, 2005; Knobloch et al, 2007).…”
Section: Theorizing On In-law’s Uncertainty and Message Processingmentioning
confidence: 99%
“…In-laws grapple with uncertainty at both the dyadic and family system level (Mikucki-Enyart, 2018, 2018a, 2018b). At the in-law level, they wrestle with relational uncertainty , defined as “the degree of confidence people have in their perceptions of involvement within close relationships” (Knobloch & Solomon, 1999, p. 264), which is comprised of a trio of uncertainties: self uncertainty , one’s own questions about involvement; partner uncertainty , doubts about the partner’s involvement; and relationship uncertainty , concerns about the nature of the relationship in general.…”
Section: Theorizing On In-law’s Uncertainty and Message Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite formal ties through the legal bonds of marriage, it is often challenging for individuals to feel as if their in-laws are a part of their family. Although research has shown that these nonvoluntary relationships can range from positive to problematic (Hess, 2000;Nuner, 2004;Serovich & Price, 1994), much of the in-law literature relates to the problems experienced in these relationships (e.g., Mikucki-Enyart, 2017;Turner, Young & Black, 2006). Several of these issues addressed by the literature surround the children of daughters-in-law (i.e., the grandchildren of mothers-in-law; e.g., .…”
Section: Introductionmentioning
confidence: 99%